Hancock Row, between Marshall Street and Creek Square, n.d. - Halliday Historic Photograph Company (Tufts Archival Research Center, 2005)
Street level view looking northwest of Hancock Row a narrow alley which runs between Marshall Street and Creek Square. This image is undated. The alley is cobblestoned. The buildings in the area are made of brick. 10 x 8 Photographs